Consumer Preference Analysis Of Melon (Cucumis Melo. L) In Traditional Markets In Karanganyar Regency - Mahananto; Prasetyo, Agung; Madiyatama, Ricko (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2023)
An increase in fruit consumption in Central Java Province occurred from 2017 to 2019. Meanwhile, from 2017 to 2021 melon production in Karanganyar Regency has decreased significantly. This is because from time to time consumer tastes tend to change. This study aims to determine the attributes of melons that are consumer preferences and which are considered by consumers in purchasing melons in traditional markets in Karanganyar district. This research method is quantitative and data analysis uses Chi Square and Fishbein Multiattributes. The results showed that the most considered attribute was the taste attribute with a calculated XÂ² value of 22.533. While the attribute that is not a preference is weight with a calculated XÂ² value of 0.533. Consumer attitudes towards the attributes of the melon fruit indicate that taste is the attribute most considered by consumers in making purchases with an attitude value of 8.88. While the price tag is an attribute that is not considered by consumers in purchasing melons.